Increased Risk of Parental Instability for Children Born Very Preterm and Impacts on Neurodevelopmental Outcomes at Age 12 - Megan E. Gath; Samantha J. Lee; Nicola C. Austin; Lianne J. Woodward (MDPI AG, 2022)
Caring for a child born preterm places significant emotional and financial burdens on family relationships. This paper examines (a) the extent to which children born very and extremely preterm are more likely to experience parental change/caregiver instability than children born full term, (b) predictors of parental change/s for preterm infants, and (c) whether exposure to parental change/caregiver instability increases child neurodevelopmental risk. Data were collected as part of a prospective longitudinal study of 110 very preterm and 113 full-term born infants and their parents studied from birth to corrected age 12 years. At ages 2, 4, 6, 9 and 12 years, detailed information was collected about the frequency and nature of all parent/caregiver changes for 3-6 monthly intervals of each child's life. At age 12, all children completed a comprehensive neurodevelopmental evaluation of their emotional and behavioural adjustment, cognition, and educational achievement. Results showed that children born very preterm were at increased risk of experiencing parental/caregiver changes, with this risk being greatest for those born extremely preterm. Neonatal medical complexity, family socioeconomic disadvantage, maternal psychological wellbeing, and child neurodevelopmental impairment were associated with a higher risk of parental change. Preterm birth and exposure to parental change/instability contributed additively to poorer child outcomes. Findings support the need for family-focused neonatal and postnatal care strategies for high-risk infants, to support parents as well as their infants to optimize child health and developmental outcomes.